Answer:
x = -2; y = 3
Step-by-step explanation:
5x + 4y = 2 (1)
3x + 3y = 3 (2)
Multiply (1) by 3 and (2) by 4
15x + 12y = 6 (3)
12x + 12y = 12 (4)
Subtract (4) from (3)
15x - 12x = 6 - 12
3x = -6
x = -6/3
x = -2
Substitute x = -2 into (1)
5x + 4y = 2
5(-2) + 4y = 2
-10 + 4y = 2
4y = 2 +10
4y = 12
y = 12/4
y = 3
The first error is when he multiplied equation (2) by 4
He didn't multiply the right hand side of the equation by 4
3x + 3y = 3 ×4
12x + 12y = 12
But he wrote
12x + 12y = 3
The the next error is subtracting the left hand side of the equation and adding the right hand side
15x + 12y = 6
12x + 12y = 3
He wrote
3x = 9
Instead of 3x = 3
Answer:
x = 34°
y = 15
Step-by-step explanation:
x + 146 = 180
x = 34°
4y + 8 + 5y + 3 + 34 = 180
9y + 45 = 180
y = 15
To find the inverse function, interchange the variables and solve for y.
f^-1(n) = 1/2 + n/3
By synthetic division, the quotient (4x^2 -10x -24)/(2x +3) is 2x -8.
___
You have not actually said what division you want performed.
Answer:
27k+3=0
Step-by-step explanation:
Write in standard form.
this way?